Literature Review: Faktor Kecemasan Matematika Siswa dan Upaya Mengatasinya - Dina, Alifa Shafira (J-PiMat : Jurnal Pendidikan Matematika, 2022)
This article was written using a literature review method that focuses on "students' mathematics anxiety factors and efforts to overcome them". Mathematics anxiety is one of the factors that affect student learning outcomes. A total of 26 articles have been analyzed to produce a literature review article. Many of these articles conducted research on SMP/MTS and SMA/SMK/MA students and research was conducted using a quantitative approach. The results of the analysis obtained the understanding of mathematics anxiety and anxiety, the factors that cause mathematics anxiety, and also how to overcome students' mathematics anxiety. There are three factors that influence math anxiety, namely personality factors, intellectual factors, and environmental factors. Students attempt to reduce the math anxiety they feel by reducing negative thinking about mathematics, being confident in their abilities, creating a relaxed and calm learning environment.